The Influence of Team Teaching Learning Model by Mind Mapping Method on the Mathematical Problem-Solving Ability - Lubna Lubna; Fitria Zana Kumala (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
The thing that underlies the implementation of this research is the low level of proficiency of class XI students at MAN Purbalingga in terms of solving mathematical problems. In this study, the researchers decided to apply appropriate learning strategies to foster skills in solving mathematical problems, namely by using the team teaching learning model with the mind mapping method. The purpose of the research conducted by researchers is to see whether there is a significant influence or not from the application of the learning model on students' skills in solving mathematical problems. This type of research is a Quasi-Experimental Design with a quantitative approach method. A total of 394 students from all students of class XI at MAN Purbalingga became the population in this study. Thirty-eight students from XI IPA 5 were assigned to be the experimental class, and 38 others from XI IPA 6 were the control class. The data collection carried out by researchers in this study was by applying an instrument in the form of a test, namely the pretest and posttest, to weigh the students' skills in solving mathematical problems. The results of the N-Gain Test conducted in the experimental class show that the average N-Gain value in that class is 0.58, which means that the class is in the medium category. Then in the control class, it is known that the average N-Gain value is 0.28, which means that the class is in a low category. From the acquisition of the average value, it is known that the experimental class shows results that are classified as superior when compared to the average value of the control class, so it can be concluded that there is an influence with the application of the team teaching learning model with the mind mapping method on the skills of students in solving mathematical problems in class XI MAN Purbalingga.